The Eyes and Ears of Sexual Exploitation Online: are Sex Buyers Part of the Prevention Puzzle to Reduce Harms in the Online Sex Industry? - Keighley, Rachel (The British journal of criminology, 2024)
UK efforts to prevent modern slavery and sexual exploitation online include assessing Adult Service Websites’ (ASWs) moderation and prevention responsibilities. Yet little is known about the role of sex buyers, as the political rhetoric assumes they are sexual offenders within the neo-abolitionist context (Serughetti 2013). Drawing from a large-scale study looking at ASWs’ responsibilities in preventing sexual exploitation online, this article shares findings from a survey with 142 sex buyers, understanding their role in this arena. Buyers possess detailed knowledge of sex working practices and indicators of exploitation. Thus, as actors in the prevention puzzle, they are uniquely positioned to understand how regulation can assist in crime prevention but equally create unintended consequences for the consensual sex industry online.